2019
DOI: 10.7759/cureus.5847
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Recent National Institutes of Health Funding in Family Medicine: Analysis Using the NIH Research Portfolio Online Reporting Tools Expenditures and Results System

Abstract: IntroductionDespite a call for increased research by family-medicine physicians, there is no data on the demographics of those awarded a National Institutes of Health (NIH) R01 grant. ObjectiveThe purpose of the study was to assess recent NIH R01 funding trends over the last decade in family medicine.Methods A retrospective analysis of NIH R01 grant funding in family medicine was conducted by extracting demographic data from the NIH’s Research Portfolio Online Reporting Tools Expenditures and Results (RePORTER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…No osteopathic physician received an NIH R01 grant in OBGYN over the time period studied. Similar to these results, no osteopathic physician has been awarded an NIH R01 grant in family medicine, general surgery, and emergency medicine over a similar time period [4][5][6]. It is unclear the reasoning behind the lack of NIH R01 grant funding in osteopathic OBGYNs, but it could be related to the lack of original research publications by osteopathic physicians in highranking OBGYN journals [7].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…No osteopathic physician received an NIH R01 grant in OBGYN over the time period studied. Similar to these results, no osteopathic physician has been awarded an NIH R01 grant in family medicine, general surgery, and emergency medicine over a similar time period [4][5][6]. It is unclear the reasoning behind the lack of NIH R01 grant funding in osteopathic OBGYNs, but it could be related to the lack of original research publications by osteopathic physicians in highranking OBGYN journals [7].…”
Section: Discussionmentioning
confidence: 68%
“…Following a similar methodology as Berg and Ashurst, an advanced search was performed using the NIH Research Portfolio Online Reporting Tools Expenditures and Results (RePORTER) search engine (http://projectreporter.nih.gov) for the "obstetrics and gynecology" keyword and the R01 activity code for the fiscal years between 2008 and 2017 [4,5]. Demographic data were collected for each PI who received an R01 award and included gender, total dollar amount awarded, medical degree (osteopathic or allopathic), dual degree (a combination of a medical degree and non-medical degree), and other degrees (PhD, DSc, MPH, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This included poor research infrastructure, representation on vital Federal committee's, low rate of Federal grants awarded and inclusion as editors in medical journals. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] A credit to our training and the make-up as a medical community; physicians tend to believe in others, favor trust and compliance. This same trait can lead to anergy at times when speaking up and taking action is more prudent.…”
Section: Editorialmentioning
confidence: 99%
“…Recent data have shown that very few osteopathic physicians serve as either the first or senior author in published original research manuscripts in emergency medicine, obstetrics and gynecology, pediatrics, and neurosurgery [1][2][3][4]. Additionally, no osteopathic physicians have been awarded a National Institutes of Health (NIH) R01 grant in emergency medicine, family medicine, general surgery, or obstetrics and gynecology in the previous decade [5][6][7][8]. Although we do not anticipate substantial differences in grants awarded to internal medicine investigators, no data currently exist on the scholarly activity between osteopathic and allopathic physicians within the specialty of internal medicine.…”
Section: Introductionmentioning
confidence: 99%